Self-Administration of Right Vagus Nerve Stimulation Activates Midbrain Dopaminergic Nuclei - Brougher, Jackson; Aziz, Umaymah; Adari, Nikitha; Chaturvedi, Muskaan; Jules, Aryela; Shah, Iqra; Syed, Saba; Thorn, Catherine A. (Frontiers in Neuroscience, 2021)
Background: Left cervical vagus nerve stimulation (l-VNS) is an FDA-approved treatment for neurological disorders including epilepsy, major depressive disorder, and stroke, and l-VNS is increasingly under investigation for a range of other neurological indications. Traditional l-VNS is thought to induce therapeutic neuroplasticity in part through the coordinated activation of multiple broadly projecting neuromodulatory systems in the brain. Recently, it has been reported that striking lateralization exists in the anatomical and functional connectivity between the vagus nerves and the dopaminergic midbrain. These emerging findings suggest that VNS-driven activation of this important plasticity-promoting neuromodulatory system may be preferentially driven by targeting the right, rather than the left, cervical nerve. Objective: To compare the effects of right cervical VNS (r-VNS) versus traditional l-VNS on self-administration behavior and midbrain dopaminergic activation in rats. Methods: Rats were implanted with a stimulating cuff electrode targeting either the right or left cervical vagus nerve. After surgical recovery, rats underwent a VNS self-administration assay in which lever pressing was paired with r-VNS or l-VNS delivery. Self-administration was followed by extinction, cue-only reinstatement, and stimulation reinstatement sessions. Rats were sacrificed 90 minutes after completion of behavioral training, and brains were removed for immunohistochemical analysis of c-Fos expression in the dopaminergic ventral tegmental area (VTA) and substantia nigra pars compacta (SNc), as well as in the noradrenergic locus coeruleus (LC). Results: Rats in the r-VNS cohort performed significantly more lever presses throughout self-administration and reinstatement sessions than did rats in the l-VNS cohort. Moreover, this appetitive behavioral responding was associated with significantly greater c-Fos expression among neuronal populations within the VTA, SNc, and LC. Differential c-Fos expression following r-VNS versus l-VNS was particularly prominent within dopaminergic midbrain neurons. Conclusion: Our results support the existence of strong lateralization within vagal-mesolimbic signaling pathways, and suggest that VNS targeted to the right, rather than left, cervical nerve preferentially activates the midbrain dopaminergic system. These findings raise the possibility that r-VNS could provide a promising strategy for enhancing dopamine-dependent neuroplasticity, opening broad avenues for future research into the efficacy and safety of r-VNS in the treatment of neurological disease.